The Hadrami Diaspora and The Network Expansion Of Majelis Shalawat In Contemporary Indonesia - Rosyid, Nur (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This paper aims to discuss the development of institutionalization of Sayyid Genealogy, Hadramiâ€™s diaspora, and its expanding network process in Indonesia contemporary Sufism. During last three decades, the Hadrami has been embarking on occupying the Islamic public by establishing majelis shalawat and organizing â€œshalawat bersamaâ€. This research was conducted towards Ahbabul Musthofaâ€™s Majelis Shalawat in Solo, Central Java. Shalawat Bersama which is introduced through the recitation of prophetic hagiography and rihlah as the way to express love and, following Bourdieuâ€™s view-as a rite to institutionalize the exclusivity of sayyid genealogy. The establishment of this Sufism religious-esthetic ethos is enabled by the economical-political historical situation of their indigenization in Indonesia. This ethnographic research showed that within the emergence of capitalism and democratic state context, Shalawat Bersama and Majelis Shalawat that thrive in the regions are not only using the media industry (audio-visual), but alsoâ€”to assumeâ€”using modern marketing logic. This logic of majelis development is concepted as a â€œreligious franchiseâ€ which means a religious movement which is based on a marketing logic through the branches established in the regions in order to promote and create direct certain religious practices supported by certain standards, especially the reference of sufistic piety and its particular performativity.Â